Becoming a school child : the role of peers in supporting new entrant transitions : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education (Early Years) at Massey University, Palmerston North, New Zealand - Hayes, Joanne Maraea (Massey University, 2013)
When children start school they are faced with the task of learning how to fit into the new environment and how to learn in new ways. The ease with which children transition to school is a factor in later academic and social success. It is therefore important that educators understand the ways successful transition experiences can be facilitated and supported. Literature describes the role of teachers in supporting transition experiences for children and the ways in which family can support children during this time. However, although research identifies a link between social skills, friendships and transition experiences, few studies have explored the role that peers play in helping new entrants learn what to do and how to learn at school. This qualitative research project aimed to address this gap and explored the role more experienced school children play in supporting the transition process for new entrants in the New Zealand context. The objectives were to identify: the ways in which more experienced peers support new entrants during their transition to school; the strategies new entrants use to learn from their peers; and the ways teachers can facilitate this learning process. A case study approach was used to examine the experiences of three children in three different schools during their early days at school. The use of classroom observations and interviews with teachers and case study children provided a range of data from different perspectives which were then thematically analysed to inform the findings. Findings presented describe the process of “intent participation” (Rogoff et al., 2003, p. 175) occurring as the new entrants moved from watching and listening to their peers to participating fully in classroom experiences. Their more experienced peers supported this process in a range of ways. Aspects of the classroom organisation and each teacher’s pedagogical practices which affected peer learning for the new entrants will be discussed and implications for educators will be explored. The findings highlight how specific contexts can influence the opportunities that arise for peer learning.
Keywords: New entrants (Education); Peer teaching; Case studies; New Zealand